A hybrid plasmid is a stable cloning vector for the cyanobacterium Anacystis nidulans R2. - Golden, S S (1983)
Anacystis nidulans R2 is a highly transformable strain which is suitable as a recipient for molecular cloning in cyanobacteria. In an effort to produce an appropriate cloning vector, we constructed a hybrid plasmid molecule, pSG111, which contained pBR328 from Escherichia coli and the native pUH24 plasmid of A. nidulans. pSG111 replicated in and conferred ampicillin and chloramphenicol resistance to both hosts. It contained unique sites for the restriction enzymes EcoRI, SalI, SphI, and XhoI, which could be used for the insertion of exogenous DNA. To demonstrate that a molecule like pSG111 could serve as a shuttle vector for the cloning of A. nidulans genes, we constructed a hybrid plasmid, pRNA404, containing an A. nidulans rRNA operon. This recombinant molecule was genetically and structurally stable during passage through A. nidulans and E. coli. The stability of the hybrid plasmid and the inserted rRNA operon demonstrates the feasibility of cloning in A. nidulans with hybrid vectors, with the subsequent retrieval of cloned sequences.